2010
DOI: 10.1007/s10552-010-9504-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in chromosomal translocation breakpoint and immune function genes and risk of non-Hodgkin lymphoma

Abstract: We found no support for a role of the studied variants in BCL2, CCND1, or MYC in risk of NHL or subtypes, but we provide further evidence of putative susceptibility loci in TNF and IL10 for specific NHL subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…Subsequently, Purdue et al (2007) was able to establish similar results, wherein, the polymorphic variations in IL-10 and TNF genes could increase the risk of NHL. Fernberg et al (2010) also described that variant alleles in IL-10-3575 (rs1800890) can increase the risk of diffuse large B-cell lymphomas, but found no associations between the polymorphisms of TNF-α-G308A (rs1800629) and the pathogenesis of DLBCL. However, this study highlighted notable associations between TNF-α-308, T-cell lymphoma and mantle cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Purdue et al (2007) was able to establish similar results, wherein, the polymorphic variations in IL-10 and TNF genes could increase the risk of NHL. Fernberg et al (2010) also described that variant alleles in IL-10-3575 (rs1800890) can increase the risk of diffuse large B-cell lymphomas, but found no associations between the polymorphisms of TNF-α-G308A (rs1800629) and the pathogenesis of DLBCL. However, this study highlighted notable associations between TNF-α-308, T-cell lymphoma and mantle cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Asian/Pacific islander patients had significantly more common involvement of extra-nodal primary sites than white or black patients. These ethnic differences may be a result of genetic or other environmental and lifestyle factors [65][66][67][68][69][70], and future exploration of them may help in elucidating the etiology of MCL. Both pleural effusions and ascites were seen in this case.…”
Section: Discussionmentioning
confidence: 99%
“…In a study recently conducted in northern Europe with 120 MCLs, TNF rs1800629 was associated with an increased risk of MCL (OR=2.8, 95% CI 1.4–5.9) [55]; however, this association was not confirmed in a large, pooled study [11]. IL10 rs1800890 was also associated with an increased MCL risk in the European study, whereas the pooled study reported that IL10 variant rs1800896 was risk-associated [56].…”
Section: Etiologymentioning
confidence: 99%